Here’s the TRIQ: The Tromsø Interest Questionnaire Based on the Four-Phase Model of Interest Development - Dahl, Tove I.; Nierenberg, Ellen (Frontiers in Education, 2021)
The Tromsø Interest Questionnaire (TRIQ) is the first suite of self-report subscales designed for focused investigations on how interest is experienced in relation to the four-phase model of interest development (Hidi & Renninger, 2006). In response to the plethora of varied interest measures that already exist in terms of theoretical grounding, form and tested quality, the TRIQ subscales were designed with a consistent form to measure general interest, situation dependence, positive affect, competence level, competence aspirations, meaningfulness and self-regulation answered in relation to some object of interest. Two studies testing the subscales’ performance using different objects of interest (self-chosen “object-general”, and pre-specified “object-specific”) provide evidence of the subscales’ internal consistency, temporal reliability and phase-distinguishing validity. Patterns across the two studies demonstrate that the TRIQ is a sufficiently reliable and valid domain-tailorable tool that is particularly effective at distinguishing phase 1 (triggered situational) from phase 4 (well-developed individual) interest. The findings raise interesting questions for further investigation about the distinction and distance between all interest phases, the push-pull factors that influence how interests evolve and additional subscales to add to the suite.